On the forecast of periodic events from incomplete records - Singh, Naunihal; Ahuja, K. L. (Defence Science Journal, 2014)
In practice several natural phenomena like wind direction, death rates, egg production ,etc. follow circular normal distribution. In this paper the problem of estimating the parameters of this distribution from incomplete records has been worked out by the method of maximum likelihood. Second order partial derivatives are given to determine the standard error of the estimates. A numerical example is added to illustrate the practical application of the method.